2011
DOI: 10.5402/2011/529876
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Perioperative Intraperitoneal Chemotherapy in Locally Advanced Colorectal Carcinoma: Preliminary Results

Abstract: Background and Aims. Intraperitoneal chemotherapy is a basic tool in the treatment of peritoneal malignancy. The purpose of the study is to investigate the effect of adjuvant perioperative intraperitoneal chemotherapy in the treatment of locally advanced colorectal cancer. Patients and Methods. Patients with T3 and T4 colorectal carcinomas that underwent R0 resection received either hyperthermic intraoperative intraperitoneal chemotherapy (HIPEC group = 40 patients) or early postoperative intraperitoneal chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 24 publications
(36 reference statements)
0
43
0
Order By: Relevance
“…This study did not show a local or distant recurrence‐free or overall survival advantage with EPIC with CRS versus CRS alone. However, the lack of hyperthermia and uneven drug distribution are potential disadvantages of EPIC versus HIPEC 14. No randomized controlled trial has been completed comparing CRS with HIPEC to CRS alone for sarcomatosis.…”
Section: Introductionmentioning
confidence: 99%
“…This study did not show a local or distant recurrence‐free or overall survival advantage with EPIC with CRS versus CRS alone. However, the lack of hyperthermia and uneven drug distribution are potential disadvantages of EPIC versus HIPEC 14. No randomized controlled trial has been completed comparing CRS with HIPEC to CRS alone for sarcomatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the size of the patient sample was limited, several randomized studies suggested that adjuvant HIPEC may significantly improve survival and reduce the incidence rate of PC in patients with gastric cancer and CRC (22)(23)(24)(25). A positive peritoneal lavage following macroscopic curative surgery in patients with CRC appears to be associated with decreased survival and increased recurrence of PM (7)(8)(9) and HIPEC appears to be a suitable treatment for patients at high risk of PM.…”
Section: Discussionmentioning
confidence: 99%
“…Tentes et al reported that patients receiving HIPEC with MMC or oxaliplatin had a better prognosis than those receiving EPIC with 5-FU (85). Based on these results, a randomized control trial for HIPEC with oxaliplatin has been initiated for patients with T4 or intra-abdominally perforated colon cancer without distant metastases (86).…”
Section: Adjuvant Intraperitoneal Chemotherapy To Prevent Peritoneal mentioning
confidence: 99%